Lacustrine Environment Reservoir Properties on Sandstone Minerals and Hydrocarbon Content: A Case Study on Doba Basin, Southern Chad - Mohd Sumery, N.F. (Institute of Physics Publishing, 2017)
The contribution of lacustrine environment as the hydrocarbon reservoir has been widely known. However, despite its growing importance, the lacustrine petroleum geology has received far less attention than marine due to its sedimentological complexity. This study therefore aims in developing an understanding of the unique aspects of lacustrine reservoirs which eventually impacts the future exploration decisions. Hydrocarbon production in Doba Basin, particularly the northern boundary, for instance, has not yet succeeded due to the unawareness of its depositional environment. The drilling results show that the problems were due to the: radioactive sand and waxy oil/formation damage, which all are related to the lacustrine depositional environment. Detailed study of geological and petrophysical integration on wireline logs and petrographic thin sections analysis of this environment helps in distinguishing reservoir and non-reservoir areas and determining the possible mechanism causing the failed DST results. The interpretations show that the correlation of all types> of logs and rho matrix analysis are capable in identifying sand and shale bed despite of the radioactive sand present. The failure of DST results were due to the presence of arkose in sand and waxy oil in reservoir bed. This had been confirmed by the petrographic thin section analysis where the arkose has mineral twinning effect indicate feldspar and waxy oil showing bright colour under fluorescent light. Understanding these special lacustrine environment characteristics and features will lead to a better interpretation of hydrocarbon prospectivity for future exploration. © Published under licence by IOP Publishing Ltd.